Systematization of nursing care in patients with heart failure stage IV - Jéssica Naiara de Medeiros Araújo; Maria Isabel da Conceição Dias Fernandes; Andréa Tayse de Lima Gomes; Millena Freire Delgado; Ana Luisa Brandão de Carvalho Lira; Allyne Fortes Vitor (Universidad de Alicante, 2017)
This is a case study, with the objective of to describe the application of the nursing process in a patient with stage IV heart failure. Conducted in a university hospital located in Northeastern Brazil. Data were collected in the month October 2012, using a structured interview and physical examination. The diagnoses identified were: Impaired skin integrity, Deprivation of sleep, Constipation and excessive fluid volume. Was traced the result - Wound healing: second intention, and applied to the nursing intervention - Care with pressure ulcers. Thus, through the implementation of the nursing care subsidized by the systematization of nursing care, it was observed that the desired results were achieved with expert.